2021
DOI: 10.3847/1538-4357/abec7e
|View full text |Cite
|
Sign up to set email alerts
|

First Observations of Anomalous Cosmic Rays in to 36 Solar Radii

Abstract: NASA's Parker Solar Probe mission continues to travel closer to the Sun than any prior human-made object, with an expected closest approach of <10 solar radii (<0.046 au) by 2024. On board, the Integrated Science Investigation of the Sun instrument suite makes unprecedented in situ measurements of energetic particles in the near-Sun environment. The current low level of solar activity offers a prime opportunity to measure cosmic rays closer to the Sun than ever before. We present the first observations of anom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 74 publications
1
10
0
Order By: Relevance
“…For example, Rankin et al. ( 2021 ) reported a helium radial intensity gradient of in the to energy range, vs. in the inner heliosphere under similar solar cycle conditions (see their Table 1). They also determined the gradient’s magnitude for specific discrete energy intervals, as shown in Fig.…”
Section: Observations Of Anomalous Cosmic Rays Inside Of 1 Aumentioning
confidence: 97%
See 2 more Smart Citations
“…For example, Rankin et al. ( 2021 ) reported a helium radial intensity gradient of in the to energy range, vs. in the inner heliosphere under similar solar cycle conditions (see their Table 1). They also determined the gradient’s magnitude for specific discrete energy intervals, as shown in Fig.…”
Section: Observations Of Anomalous Cosmic Rays Inside Of 1 Aumentioning
confidence: 97%
“…Figure adapted from Rankin et al. ( 2021 ) (Helium) and Rankin et al (in press) (Oxygen)
Fig. 11 Radial gradients of PSP/ISOIS helium as a function of energy.
…”
Section: Observations Of Anomalous Cosmic Rays Inside Of 1 Aumentioning
confidence: 99%
See 1 more Smart Citation
“…It is reported that the observed GCR radial intensity gradients are much smaller than that of ACRs, which is probably due to the difference between their charge states (e.g., Cummings et al 1987;Leske et al 2005). Based on the recent observations from Parker Solar Probe, Rankin et al (2021) have studied the radial gradient of ACRs in to ∼36 solar radii (0.166 au) and reported that the radial gradients of ACR helium at energies of ∼4 to ∼45 MeV nuc −1 are larger than previous observations made further out in the heliosphere.…”
Section: Introductionmentioning
confidence: 96%
“…Energetic particles commonly observed in the heliosphere are composed of solar energetic particles (SEPs, also known as solar cosmic rays, with energies of a few keV up to several GeV, Fu et al 2019), Galactic cosmic rays (GCRs, with energies of tens of MeV nuc −1 up to 10 14 MeV nuc −1 , Heilbronn 2021), and anomalous cosmic rays (ACRs, with energies of ∼5-50 MeV nuc −1 , Rankin et al 2021).…”
Section: Introductionmentioning
confidence: 99%